Pelvic Ewing's Sarcoma: A Review from Scottish Bone Tumour Registry - S Bhagat; H Sharma; DS Pillai; MJ Jane (Journal of Orthopaedic Surgery, 2008)
Purpose. To review various treatment modalities on outcome of patients with pelvic Ewing's sarcoma. Methods. Between January 1948 and December 2004, 18 male and 15 female patients aged 3 to 48 (mean, 20) years with pelvic Ewing's sarcoma were retrospectively reviewed from the Scottish Bone Tumour Registry. Results. The commonest site involved was the ilium. The main presenting symptom was pain, followed by swelling and restricted hip movements. Treatments included surgery, radiotherapy, chemotherapy, or any of them in combination. Patients who had no metastasis at presentation (p<0.01) and underwent chemotherapy with ifosfamide (p<0.01) had significantly longer survival. Age (p=0.09), gender (p=0.95), delay in presentation (p=0.31), tumour site (p=0.9), surgery (p=0.73), and radiotherapy (p=0.23) were not predictive of survival in the univariate analysis. The 5-year event-free survival rate in patients with no metastasis at presentation was 35%. Conclusion. Intense multi-agent neo-adjuvant chemotherapy including ifosfamide followed by wide excision and postoperative radiation are recommended. Local therapy should not take precedence over or interfere with systemic chemotherapy.